A New 3D-Regular Shaped Geometry-Based MIMO Channel Model for Vehicle-to-Vehicle Communications in Rectangular Tunnel - Chebil, Jalel; Zormati, Hanene; Mansour, Ali; Ben Mabrouk, Ismail; Bel Hadj Tahar, Jamel (2025)
The intelligent transportation systems have attracted the attention of many researchers and developers in the last few decades in order to make the exploitation of transportation networks be safer, more coordinated, and smarter. Channel modeling for vehicle-to-vehicle (V2V) communication is one of the related research topics that are being investigated in this field. In this paper, a three-dimensional wideband regular shaped geometry based channel model for multiple-input and multiple-output V2V communication channel is proposed for rectangular tunnel environments. A two semi-circular geometry is adopted to describe moving vehicles around transmitter and receiver, and a cuboid model is employed to depict scatterers located on internal surfaces of the tunnel walls. Using this channel model, the channel characteristics including space time correlation function, frequency correlation function and auto-correlation function are determined and simulated numerically. Then, the results are compared with the derived statistics from Avazov et al. and Zhou et al. methods to prove the efficiency of the proposed model.
Keywords: Channel model; MIMO channel; Rectangular tunnel; Vehicle-to-vehicle communication